Bioinformation (Biomedical Informatics Pub. Group, 2005)
Bioinformation publishes original research articles in all aspects of biological knowledge discovery through mathematical and computational analysis of biological data. The journal specifically invites articles describing new biological insights based on primary or derived data.
Keywords: biologie; Computational Biology; výpočetní biologie